Nongeminate Recombination Dynamics–Device Voltage Relationship in Hybrid PbS Quantum Dot/C60 Solar Cell - Marín-Beloqui, José Manuel (American Chemical Society, 2013)
Here we employ transient optoelectronic techniques to study the charge present in the device and the nongeminate recombination rate in hybrid PbS/C60 planar heterojunction solar cells under working conditions. We find that in low light intensity conditions there are very few charges present in the solar cell and that the charge increases linearly with voltage, suggesting that most of the charge resides at the electrodes (capacitive charges). At higher applied light bias, the charges stored in the device increase exponentially. The carrier lifetime is very short (τ < 1 us at 1 sun; 1 sun = 100 mW/cm2 of sun-simulated light) when compared to organic solar cells. By correlating the charge carrier lifetime with the device charge density, we successfully reconstruct the photocurrent− voltage (J−V) curve at 1 sun, demonstrating that fast nongeminate recombination losses limit the efficiency in these quantum dot-based devices.
Keywords: Células solares; Puntos cuánticos; PbS; Quantum Dot; Solar Cell